Kinerja Pegawai Harian Tidak Tetap (Phtt) Dinas Pendidikan Dan Kebudayaan Kabupaten Enrekang - Nurhikma, Nurhikma; Razak, Andi Rosdianti; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the performance of daily non-permanent employees of the Education and Culture Office of Enrekang Regency. The number of informants in this study were 8 people. This study used a qualitative type with a phenomenological research l that emphasized the subjectivity of human life experiences. Data collection techniques using the method of observation, interviews and documentation. This study used triangulation of time sources and techniques to check the validity of the data. The data analysis used the component of reduction, data presentation, and conclusion . The data collection technique used the interview observation method and documentation. The results showed that the performance of daily non-permanent employees at the Education and Culture Office of Enrekang Regency which had not all indicators applied All indicators namely Productivity, Service Quality, Responsiveness and Responsibility even though it had been running according to the existing SOP in the office but there were still complaints of service by the community, especially l the teacher who had an interest in its services and its completion as well as office infrastructure.Keywords: Performance, Productivity, Responsiveness, Employees